Entrepreneurs and passion for business / Nurul Hayani Abd Rahman, Dr. Rabitah Harun and Nurul Fazila Abd Rahman - Abd Rahman, Nurul Hayani; Harun, Rabitah; Abd Rahman, Nurul Fazila (Universiti Teknologi MARA, Kedah, 2022)
Entrepreneurs are active in a wide range of industries that benefit the nation. They produce goods and services for the domestic and global markets to meet consumer demands. They are uniquely capable of recognising business opportunities and envision how they can be realised. They require passion as their driving force to accomplish this. Entrepreneurs are passionate about what they do. This passion is essential to their entrepreneurial activity. Success is propelled by passion. It is one of the most important qualities that all successful entrepreneurs must possess. It is about their ambition and their passion for what they do, which provides them with a unique perspective on the world that few others share. In other words, passion is a strong desire for an activity that many individuals value highly, enjoy fervently, and are willing to invest time and effort to pursue (Vallerand et al., 2003). Entrepreneurial passion is the positive emotion that entrepreneurs possess toward entrepreneurial work (Ho & Pollack, 2014). This has become one of the most crucial affective experiences to be gained by entrepreneurs (Stroe, 2017) with different types of passion lead to different outcomes on entrepreneur subjective well-being (Bayraktar & Jiménez, 2022) and entrepreneur intention (Murad et al., 2021).